2020
DOI: 10.3389/feduc.2020.582882
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of the COVID-19 Pandemic on Student Wellbeing at Universities in the United Kingdom: A Conceptual Analysis

Abstract: Transitioning into the university environment can be both exciting and stressful for new and returning students alike. The pressure to perform well academically in an increasingly competitive environment, coupled with a vast array of lifestyle changes, can contribute to suboptimal wellbeing. Over recent years, uptake to wellbeing services within universities in the United Kingdom has grown given the concurrent rise in mental health difficulties reported. Higher education students now have to contend with a dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 61 publications
5
144
1
7
Order By: Relevance
“…Several population-based surveys have also revealed that students report a higher prevalence of depressive, anxiety and stress symptoms [27,28]. Studies on student populations throughout the world [29][30][31], including in Malaysia [32], have shown that the COVID-19 pandemic has put a strain on their mental health. The main reasons for students experiencing heightened psychological distress include economic effects, changes in academic activities, difficulties adapting to online distance learning methods and uncertainty about the future with regard to academics and careers.…”
Section: Plos Onementioning
confidence: 99%
“…Several population-based surveys have also revealed that students report a higher prevalence of depressive, anxiety and stress symptoms [27,28]. Studies on student populations throughout the world [29][30][31], including in Malaysia [32], have shown that the COVID-19 pandemic has put a strain on their mental health. The main reasons for students experiencing heightened psychological distress include economic effects, changes in academic activities, difficulties adapting to online distance learning methods and uncertainty about the future with regard to academics and careers.…”
Section: Plos Onementioning
confidence: 99%
“…Wills-Herrera et al (2009) argued that the interaction amongst individual, social and culture and how these multidimensional variables interact with each other affect an individual's development. In higher education, many researchers primarily focused on student well-being (e.g., Burns et al, 2020;Cooke et al, 2006;Salami, 2010). To highlight a few, Zhai andDu (2020), andElmer et al (2020) focused on the issue of student well-being in the dynamic of mental health.…”
Section: Cultivation Of Whole Person Development Through Online Learningmentioning
confidence: 99%
“…Amidst the already growing challenges of the COVID-19 in the development of student competence, the impacts of the COVID-19 pandemic are further magnified on students’ mental and physical wellbeing (Burns et al., 2020). The shift from the conventional face-to-face classroom to online learning has challenged students’ ability to transition under the COVID-19 circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The partial closure of universities, remote delivery of teaching and support services, social isolation of students who are unable to return home, and the level of uncertainty regarding teaching and support are all suggested to have impacted the mental health and wellbeing of university students (Burns et al, 2020). Consequently, there has been a clear demand for universities to develop action plans to address mental health issues that have been caused or exacerbated by COVID-19 (Zhai and Du, 2020).…”
Section: The Impact Of Covid-19mentioning
confidence: 99%